2022
DOI: 10.3390/healthcare10040678
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on the Cultural Competence of Nurse Practitioners and Its Affecting Factors

Abstract: Cultural competence refers to a healthcare provider’s ability to consider cultural factors that affect an individual’s health and attitudes toward disease and disability. Nurse practitioners (NPs) are increasingly important in healthcare, practicing culturally competent care strategies to improve the quality of patient care. The aim of this study was to explore cultural competence and its related factors among NPs. A cross sectional study design with a structured questionnaire survey was used. Purposive sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
0
0
1
Order By: Relevance
“…Additionally, experience with national policies, programs, and proclamations concerning patient rights and medicolegal issues, as well as measures taken, may also have contributed to these differences. Similarly, the findings of this study are lower than those reported in studies conducted in Canada [ 6 ] and Taiwan [ 28 ]. This variance could potentially be attributed to differences in sample size, nurse and patient awareness of cultural diversity, clinical settings, trends in patient-centered care, and experience with national policies, programs, and proclamations concerning patient rights and medicolegal issues.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Additionally, experience with national policies, programs, and proclamations concerning patient rights and medicolegal issues, as well as measures taken, may also have contributed to these differences. Similarly, the findings of this study are lower than those reported in studies conducted in Canada [ 6 ] and Taiwan [ 28 ]. This variance could potentially be attributed to differences in sample size, nurse and patient awareness of cultural diversity, clinical settings, trends in patient-centered care, and experience with national policies, programs, and proclamations concerning patient rights and medicolegal issues.…”
Section: Discussioncontrasting
confidence: 98%
“…In this study, the cultural competence subscale with the highest score was cultural awareness, a trend consistent with findings from the USA [ 8 ], Austria [ 10 ], Taiwan [ 24 , 28 ], Indonesia [ 26 ], and Assossa in western Ethiopia [ 15 ]. However, cultural knowledge emerged as the subscale with the lowest score, mirroring a study conducted in Taiwan [ 24 ].…”
Section: Discussionsupporting
confidence: 88%
“…In the study of Debiasi and Selleck (2017), there is a noticeably higher percentage of nursing practitioners documenting cultural assessment and a significantly lower percentage of stereotyping. The study by Liu et al (2022) suggests that providing learning and training opportunities can improve cultural competence, and therefore, nurses can give better culturally appropriate care.…”
Section: Discussionmentioning
confidence: 99%
“…Es por lo anterior, que la validación de intervenciones que incorporen no solo las necesidades educativas frente a la prevención de enfermedades como la malaria, sino también las características de diversidad cultural de los pueblos indígenas, genera aportes signicativos para la profesión de enfermería, al tener en cuenta que una atención culturalmente competente mejora la calidad de esta misma (34).…”
Section: Discussionunclassified